2009
DOI: 10.1007/s00244-009-9436-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Validation of Two Chromatographic Methods (HPLC-Fluorescence and LC–MS/MS) for the Determination and Confirmation of Ochratoxin A in Pig Tissues

Abstract: Two different analytical methods for the determination and confirmation of ochratoxin A (OTA) in blood serum, kidney, and liver of pigs have been compared. Sample cleanup was based on liquid-liquid phase extraction. The detection of OTA was accomplished with high-performance liquid chromatography (HPLC) combined either with fluorescence detection (FLD) or electrospray ionization (ESI+) tandem mass spectrometry (MS/MS). The comparative method of evaluation was based on the investigation of 90 samples of blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It is worth noting that these prior studies used an HPLC fluorescence detection assay for pyridinoline quantification as opposed to the LC-MS technique used in this paper. Because LC-MS methods have repeatedly been shown to be more precise and accurate than HPLC fluorescence detection methods [54][55][56] , future characterization studies on native fibrocartilage crosslinks using LC-MS would yield more comparable data to those collected by our study. Overall, TCL + LPA treated neomenisci exhibited crosslink content that appears to meet or exceed values reported in the literature, though characterization of native tissue via LC-MS methods is warranted.…”
Section: Discussionmentioning
confidence: 70%
“…It is worth noting that these prior studies used an HPLC fluorescence detection assay for pyridinoline quantification as opposed to the LC-MS technique used in this paper. Because LC-MS methods have repeatedly been shown to be more precise and accurate than HPLC fluorescence detection methods [54][55][56] , future characterization studies on native fibrocartilage crosslinks using LC-MS would yield more comparable data to those collected by our study. Overall, TCL + LPA treated neomenisci exhibited crosslink content that appears to meet or exceed values reported in the literature, though characterization of native tissue via LC-MS methods is warranted.…”
Section: Discussionmentioning
confidence: 70%
“…Pyridinoline crosslink content normalized to dry weight trended highest in the central region of the medial minipig meniscus and was measured at approximately 0.16%, which is higher than levels obtained in human menisci using an HPLC fluorescence detection assay at 0.12% ( Takahashi et al, 1998 ). It should be noted that values in the present study were obtained using an LC-MS method, which has been shown to be more precise and accurate than HPLC fluorescence detection methods ( Milićević et al, 2010 ; Wang et al, 2012 ; Bandeira et al, 2013 ; Bielajew et al, 2020 , 2021 ). Pyridinoline crosslink content, for example, has been quantified using LC-MS techniques in bovine articular cartilage, showing crosslink levels of 0.12% of total dry weight, which were on par with values recorded in this study ( Espinosa et al, 2021a ).…”
Section: Discussionmentioning
confidence: 80%
“…Other solvents have been used in recent years for mycotoxin LLE from organs and tissues. For instance, OTA was extracted using CH 2 Cl 2 [ 120 ] and by a solvent mixture of ice-cold absolute ethanol/trichloroacetic acid [ 121 ] from pig and rat samples; plasma, liver, and kidney, respectively.…”
Section: Resultsmentioning
confidence: 99%